PENERAPAN MODEL BLENDED LEARNING DENGAN PENDEKATAN FLIPPED CLASSROOM PADA PEMBELAJARAN PAI DI MTs NURUL HASAN SUMBERAGUNG - Hariyadi, Mochamad; Burhanuddin, Hamam (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the development process and integration process of Islamic boarding school values, as well as the rationale for developing a blended learning model based on Islamic boarding school values in Islamic Religious Education (PAI) at MTs Nurul Hasan Sumberagung, within the Nurul Hasan Islamic Boarding School. This study employed a qualitative approach with a case study approach. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis employed an interactive model encompassing data reduction, data presentation, and conclusion drawing, with data validity tested through source and technique triangulation. The results indicate that the development of blended learning was carried out through a combination of computer laboratory-based learning and face-to-face learning based on halaqah (religious group discussions). Students were not permitted to bring mobile phones, so digital learning access was conducted in a scheduled and controlled manner in the computer lab. The integration of Islamic boarding school values such as etiquette, discipline, responsibility, and deliberation was carried out at every stage of learning, from planning, implementation, and evaluation. This model was developed in response to the needs of 21st-century digital literacy without ignoring the characteristics and culture of Islamic boarding schools. This study concludes that the development of blended learning based on Islamic boarding school values can be an adaptive learning model that harmoniously integrates technology and Islamic boarding school traditions. This model contributes to improving the quality of Islamic Religious Education (PAI) learning while strengthening the character of students in Islamic boarding school-based madrasah environments.